Usability Analysis of the DKI Jakarta Online Tax Application Using the System Usability Scale (SUS) Method - dimas faris noorfauzi; Muhammad Al-Makky; Kusuma Adi Ahmad (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
The DKI Jakarta Online Tax Application is an application launched by the Jakarta City government to make it easier for the public in terms of renewing STNK, BPKB, and annual tax for both two-wheeled and four-wheeled vehicles, and much more. This application functions to speed up the long offline process by simply accessing the application and including the vehicle number to get a queue ticket or check prices. This research was conducted by collecting primary data through questionnaires to a total of 400 respondents who are DKI Jakarta residents who use the DKI Jakarta Online Tax application to determine the level of user satisfaction with the DKI Jakarta Online Tax application for the City of Jakarta using Usability Testing and System Usability Scale (SUS), the number of respondents this is sufficient based on the calculation of the number of samples from the existing population. The results of this study indicate that the DKI Jakarta Online Tax application gets a score of 50.31 with a "Very Bad" rating so it really needs improvement and improvement of the quality of the application so that it can be accepted and used properly by the community. Researchers also provide several recommendations to improve the usefulness of the DKI Jakarta Online Tax application.Keywords: Pajak Online DKI Jakarta; Usability Testing; System Usability Scale; SPSS AbstrakAplikasi Pajak Online DKI Jakarta merupakan aplikasi yang diluncurkan oleh pemerintah Kota Jakarta untuk mempermudah masyarakat dalam hal perpanjangan STNK, BPKB, dan pajak tahunan kendaraan baik roda dua maupun roda empat, dan masih banyak lagi. Aplikasi ini berfungsi untuk mempercepat proses offline yang begitu lama dengan hanya mengakses aplikasi tersebut dan mencantumkan nomer kendaraan untuk mendapatkan tiket antrian atau pengecekan harga. Penelitian ini dilakukan dengan pengumpulan data primer melalui kuisioner kepada total 400 responden yang merupakan masyarakat DKI Jakarta pengguna aplikasi Pajak Online DKI Jakarrta untuk mengetahui tingkat kepuasan pengguna terhadap aplikasi Pajak Online DKI Jakarta Kota Jakarta menggunakan Usability Testing dan System Usability Scale (SUS), jumlah responden ini sudah cukup berdasarkan perhitungan jumlah sampel dari populasi yang ada. Adapun hasil dari penelitian ini menunjukkan bahwa aplikasi Pajak Online DKI Jakarta mendapat skor 50,31 dengan peringkat “Buruk Sekali” sehingga sangat diperlukan perbaikan dan peningkatan kualitas aplikasi agar dapat diterima dan dipergunakan dengan baik oleh masyarakat. Peneliti juga memberikan beberapa rekomendasi untuk meningkatkan kegunaan aplikasi Pajak Online DKI Jakarta.